Barriers to Health Care Communication: Patient Education Resource Readability and Spanish Translation for Slipped Capital Femoral Epiphysis - Emma Danielle Grellinger, BS; Ishaan Swarup, MD (Journal of the Pediatric Orthopaedic Society of North America)
ABSTRACT: Background: The American Medical Association and the National Institutes of Health recommend that patient education resources be written at sixth- and eighth-grade reading levels, respectively. However, many existing resources are written above this level. In addition, the majority of patient education resources are only available in English, despite the significant Spanish-speaking population in the United States. The purpose of this study was to determine the availability and readability of online patient education resources for slipped capital femoral epiphysis (SCFE) provided by the top-ranked pediatric orthopaedic hospitals and major pediatric orthopaedic professional societies. Methods: We performed a cross-sectional analysis to determine the availability of English and Spanish language resources for SCFE provided by the top pediatric orthopaedic hospitals and major professional societies. We then assessed the readability of available patient education materials via 3 measures of readability. Statistical analysis was performed using descriptive, univariate, and correlation analyses. Results: In total, 79.6% (39/49) of hospitals and 66.7% (2/3) of professional societies provided English language resources for SCFE. In contrast, Spanish language resources were provided by 34.7% (17/49) and 33% (1/3) hospitals and professional societies. English language resources scored significantly lower than Spanish language resources using the Flesch-Kincaid and Fernandez-Huerta reading ease scales, respectively (60.32 vs 65.89, P < .05). There was no difference in grade level calculated by Fry Graph/Gilliam-Peña-Mountain (9.5 vs 8.5, P > .05), but English language resources had a significantly higher grade level calculated by SMOG/SOL (11.9 vs 10.4, P < .01). There was greater availability of Spanish language resources in states with >20% primary Spanish speakers (P < .05). Conclusions: The majority of top-ranked hospitals and professional societies provide online educational materials on SCFE in English; however, only a third provide similar materials in Spanish. Additionally, the average reading level of English and Spanish language resources is above the recommendations from the American Medical Association and National Institutes of Health. Additional effort and resources should be allocated toward improving SCFE patient education materials to increase accessibility to broader patient and caregiver populations. Key Concepts: (1) Online patient education resources for slipped capital femoral epiphysis (SCFE) are written above the recommended reading grade level for both English and Spanish. (2) There is limited availability of Spanish-language patient education recourses for SCFE, despite the significant Spanish-speaking population in the United States. (3) There is greater availability of Spanish language resources for SCFE in states with a primary Spanish-speaking population >20%. Level of Evidence: III